2000
DOI: 10.1016/s0921-8009(00)00179-8
|View full text |Cite
|
Sign up to set email alerts
|

Air quality and economic growth: an empirical study

Abstract: This study has been observed an inverse (and sometimes U-shaped) relationship between environmental degradation and per capita real income as opposed to the inverted U-shaped environmental Kuznets curve (EKC) found in many earlier studies. It was felt that a possible explanation of the observed pattern of relationship might be sought in the dynamics of the process of economic growth experienced by the countries concerned. Economic development may strengthen the market mechanism as a result of which the economy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(91 citation statements)
references
References 22 publications
2
85
0
4
Order By: Relevance
“…The amounts of turning points in sulfur emissions were quite low in almost all studies. The study of Dinda et al (2000) showed comparatively lower turning point income ($3000-6000 in 1985 dollars).…”
Section: Ekc For Soxmentioning
confidence: 91%
See 1 more Smart Citation
“…The amounts of turning points in sulfur emissions were quite low in almost all studies. The study of Dinda et al (2000) showed comparatively lower turning point income ($3000-6000 in 1985 dollars).…”
Section: Ekc For Soxmentioning
confidence: 91%
“…Yet their studies have shown a medium amount of turning point which is greater than that of Panayotou (1997), Dinda et al (2000), etc. Of note is the fact that developing countries have shown lower income per capita for turning point than developed ones.…”
Section: Gems Stands For Global Environment Monitoring System It Wasmentioning
confidence: 95%
“…In our general empirical specification, we control for the share of manufacturing production in the GDP. A higher share of value added in the industry and manufacturing may be accompanied by higher emissions (Dinda et al, 2000;Friedl and Getzner, 2003). We also account for the efficiency of energy consumption.…”
Section: Independent Variablesmentioning
confidence: 99%
“…[8] perform an empirical analysis of international variations in seven indicators of air and water quality finding that literacy, political rights, and civil liberties have particularly strong effects on environmental quality in low-income countries. [9] find that a more capital intensive production technique (a higher per capita income level) would cause less pollution.…”
Section: Introductionmentioning
confidence: 88%